"Você teve algum(a) professor(a) com deficiência na sua formação?" - Trajetórias de professoras surdas na docência da educação superior - TAMIRIS LOPES FERREIRA (2022)
In recent years, Higher Education Censuses have pointed to a shortage of teachers with disabilities working in Brazilian universities. Added to this, we also observed a lack of studies regarding the performance and working conditions of these teachers. In this sense, we aimed with this research, from the perspective of Historical-Cultural Psychology, to understand the trajectory of deaf university professors with regard to the process of inclusion in the teaching activity. For that, as a methodology, we used bibliographical research and case study, developing our investigations from the interview with two deaf university professors. In the first section, we present the studies collected in the bibliographic survey carried out in the Brazilian Digital Library of Theses and Dissertations and in the Redalyc database - Red de Revistas Científicas de América Latina y el Caribe, España and Portugal. From the reading and analysis of the findings, we found that the bibliography about the subject is scarce, being built as we follow a recent path of legal achievements in the field of public policies aimed at people with disabilities. In the second section, we present the historical aspects that relate to the educability of people with disabilities and, specifically the educability of deaf people, and then we focus on the insertion of people with disabilities in the job world, having as a starting point the legislative path. In this organization we identify the contradictions and historical marks that expose the dialectic of inclusion-exclusion of people with disabilities in their schooling process and access to the job world. In the third section of this study, we aimed to address the contributions of historical-cultural psychology in relation to our research object, explaining about Vygotskian defectology and the inclusion process, focusing on deafness and hearing impairment; in addition to briefly addressing the concept of experience in historical-cultural psychology. In the fourth section, we address the methodological procedures of the study on screen, presenting the procedures adopted in carrying out the empirical research and the stage of analysis and interpretation of the interviews with Sol and Estrela, deaf university professors who live in the Midwest region of our country. As a result of our research, we concluded that the absence of teachers with disabilities in university education is related to the lack of concrete conditions and possible paths for their humanization in different social contexts. We hope that our research can contribute to the scientific field with regard to the production of knowledge about disability and deafness, offer subsidies for the critical performance of school psychologists in the field of Special Education from the Perspective of Inclusive Education and promote the organization of more inclusive practices in the university context, considering all the people who are part of the academic community.